The impact of clothing style on bone mineral density among post menopausal women in Morocco: a case-control study - Saoud Bouchra; Aichaoui Siham; Allali Fadoua; Maaroufi Houda; Abouqal Redouane; Hajjaj-Hassouni1 Najia (BMC, 2006)
Abstract Background The clothing style is an important factor that influences vitamin D production and thus bone mineral density. We performed a case-control study in order to evaluate the effect of veil wearing (concealing clothing) on bone mineral density in Moroccan post menopausal women. Methods The cases were osteoporotic women whose disease was assessed by bone mineral density measurement. Each patient was matched with a non osteoporotic woman for age, and body mass index. All our patients were without secondary causes or medications that might affect bone density. The veil was defined as a concealing clothing which covered most of the body including the arms, the legs and the head. This definition is this of the usual Moroccan traditional clothing style. Results 178 post menopausal osteoporotic patients and 178 controls were studied. The mean age of the cases and the controls was 63.2 years (SD 7) and the mean body mass index was 32.1 (SD 8). The results of crude Odds Ratios analyses indicated that wearing a veil was associated with a high risk of osteoporosis: OR 2.29 (95% CI, 1.38-3.82). Multiparity or a history of familial peripheral osteoporotic fractures had also a significant effect on increasing the osteoporosis risk (ORs: 1.87 (95% CI, 1.05-3.49) and 2.01 (95% CI, 1.20-3.38)). After a multiple regression analysis, wearing the veil and a history of familial osteoporotic fractures remained the both independent factors that increased the osteoporosis risk (ORs: 2.20 (95% CI, 1.22-3.9) and 2.19 (95% CI, 1.12-4.29) respectively). Conclusion our study suggested that in Moroccan post menopausal women, wearing a traditional concealing clothing covering arms, legs and head increased the risk of osteoporosis. Further studies are required to evaluate the clinical impact of the above findings and to clarify the status of vitamin D among veiled women in Morocco.